Interpretasi Hukum “Anak Di Luar Perkawinan” Dalam Undang-Undang Perkawinan 1974 (Studi Pandangan Hakim Pengadilan Agama Provinsi Daerah Istimewa Yogyakarta) - Mahmud Mahmud (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2019)
This research was conducted with the aim to findout what the judge's view of the legal interpretationabout the outside marriage state of children and howthe interpretation of the judge's judgments regardingthe decision of the panel judges related to the outsidemarriage state of children according to the state viewsof the Religious Courts of Yogyakarta Special Province.In this method of study using the Juridical Sociologicalmethod that a combination of fields that use primarydata and secondary data in the form of interviews withinformants and this study is descriptive analytical.Based on the approach method concluded: 1. Accordingto the marriage law Law No. 1 of 1974 in Chapter IX,Article 43 paragraph (1) a child out of wedlock only hasa civil law with his mother and his mother's family. Butwith the decision of the constitutional court No. 46 /PUUVIII / 2010 read: "Children born outside ofmarriage have a civil relationship with their mothersand families and with men as fathers who can be provenby knowledge and technology or by other meansaccording to the law so that they are proven to haveblood relations, or a civil relationship with his father'sfamily, not enough to give consideration to the judge indeciding the case, according to the author, it is quiteinteresting to understand the state of children outsidethe marriage from the point of view of the judge. In thisresearch, the compiler tried to study it using fieldresearch. The primary material of this research is the viewsof the judges in the Bantul Religious Courts, Yogyakartaand Sleman. Regarding the legal interpretation by thejudge of the state of children outside of marriage, in themarriage law No. 1 of 1974 obtained by interview.Based on the analysis carried out, it can be obtainedfrom the Judges in the Bantul Religious Courts,Yogyakarta and Sleman have the same view regardingthe legal interpretation of the state of children outsideof marriage. that the definition of a child outsidemarriage is a child of the sirri marriage. The equation isin his view that what is seen first is certainly thelegitimacy of his marriage, where when the terms andconditions are fulfilled, the request is granted andwhere there is an unfulfilled meal, it will be rejected.Keywords: Outside marriage of Children, interpretationof law, laws